PENDUGAAN PERKEMBANGAN ALFISOLS DI KECAMATAN JATIPURO, KARANGANYAR DENGAN MODEL KESTABILAN GENETIK - Raditia Eka Kurniawan; Sudjono Utomo; Mujiyo Mujiyo (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2011)
Title : The Development Prediction and Differentiated Alfisols at Jatipuro Sub District of Karanganyar with Genetic Stability Model. This research had been conducted at Jatipuro, Sub district of Karanganyar from July until September, 2007. The aim of this research are to know and comparing the development of Alfisols with genetic stability model. This research was descriptive‐explorative research, and the variables approached by field’s survey and supported by laboratory analysis. The site sampling on the fields determined with soil mapping unit. Samples for physical, chemicals and sand mineralogy properties was take from representative pedon or profile from each soil mapping unit. This research uses statistical analysis stepwise regression to know which the most variable can explain the soil development, and the Eberhart‐Russell’s genetic stability model to determine the degree of soil stability for any soil mapping unit. The result of this research can be concluded that the 3rd soil mapping unit (NGEPUNGSARI series, Ultic Hapludalfs, very fine, kaolinitic, active, non acid, isohyperthermic family) was the most’s stable in soil development, and followed by 1st soil mapping unit (JATISOBO series, Vertic Hapludalfs, very fine, kaolinitic, active, non acid, isohyperthermic family). Even though, the 2nd soil mapping unit (JATISUKO series, Typic Hapludalfs, very fine, kaolinitic, active, non acid, isohyperthermic family) was the most’s unstable in soil development. Each soil mapping unit also showed the difference of soil development, that looking from the endogen and exogen’s factors can be explained. Keywords: Alfisolfs, development, differentiated, Genetic Stability Model